Diagnostic Yield and Complications of Transthoracic CT-Guided Biopsies - Devkota, Ganesh; Gautam, Mahesh; Bhattarai, Ashish Mohan; Tripathi, Pratiksya (Journal of Nobel Medical College, 2026)
Background: Transthoracic Computed Tomography-guided lung biopsy is a minimally invasive and reliable procedure for evaluating pulmonary lesions. This study aimed to determine the diagnostic yield and analyze complications related to transthoracic Computed Tomography -guided lung biopsy.Materials and Methods: A prospective study was conducted on 65 patients undergoing Computed Tomography-guided transthoracic lung biopsy using a 128-slice Siemens scanner. A 17-gauge coaxial introducer and an 18-gauge semi- automated core needle were used. Lesion size, depth, diagnostic adequacy, histopathological outcomes, and complications were recorded.Results: Among 65 patients who underwent the computed tomography biopsies of lung lesions, adequate tissue was obtained in 63/65, i.e. diagnostic yield was 96.9%. Among these, 52 cases (82.5%) were malignant, with adenocarcinoma (n=26, 41.3%) and squamous cell carcinoma (n=14, 22.2%) being the most frequent. Benign lesions accounted for 11 cases (17.5%), including 9 cases of pulmonary tuberculosis and 2 of organizing pneumonia. Lesion characteristics affected diagnostic success: smaller lesions (5 cm from pleura) were associated with lower yield. Complications occurred in 18 patients (27.7%), with pneumothorax being the most common (10/18, 55.5%), though only 2 cases required chest tube insertion. Other complications included hemoptysis (5 cases) and parenchymal hemorrhage (3 cases). Increased complication risk was observed in patients with emphysematous lungs, smaller lesions, and greater lesion depth.Conclusion: The findings of this study suggest that, Computed Tomography-guided percutaneous biopsy of pulmonary lesions using an 18-gauge coaxial semi-automated core needle is a safe, minimally invasive, and reliable diagnostic technique, demonstrating high accuracy with a low rate of clinically significant complications, and is well-suited for the evaluation of suspected lung pathology.